Anti-Mullerian hormone trend evaluation after laparoscopic surgery of monolateral endometrioma using a new dual wavelengths laser system (DWLS) for hemostasis. (2nd January 2016) - Nappi, Luigi; Angioni, Stefano; Sorrentino, Felice; Cinnella, Gilda; Lombardi, Michela; Greco, Pantaleo
Abstract: Operative laparoscopy is the gold standard in the treatment of endometriotic ovarian cysts. Excisional surgery is the best technique to prevent recurrences and improve symptoms but it may result in ovarian reserve damage due to the removal of healthy ovarian cortex. The aim of this study was to assess the impact on ovarian reserve of the use of dual wavelengths laser system (DWLS) hemostasis after stripping technique of monolateral endometrioma, by dosing the anti-Mullerian hormone (AMH). This prospective study was conducted at the Institute of Obstetrics and Gynecology, University of Foggia, from December 2013 to January 2015. Forty-five women underwent excision of monolateral endometriotic ovarian cyst by stripping without using a bipolar coagulation and performing hemostasis with a DWLS. The AMH serum levels were estimated before the surgery (T0), 4–6 weeks (T1) and 6–9 months (T2) after surgery. Our results suggest that an appropriate surgical technique with the use of laser hemostasis does not determine a significant reduction of ovarian reserve. Laser hemostasis could prevent follicular reserve loss after ovarian endometrioma surgery.